1147 Prehospital oral trans-mucosal fentanyl citrate: preliminary experience and possible implications for civilian mass casualty response. Issue 3 (21st February 2022) - Carenzo, Luca; McDonald, Adam; Grier, Gareth
Abstract : Aims/Objectives/Background: *The data below is pre-publication at the time of abstract submission* There is scope for improving medical care, including analgesia provision, in the pre-hospital phase of civilian mass casualty incidents (MCIs). The oral trans-mucosal fentanyl citrate (OTFC) lozenge has previously been identified as a possible method to address this need. Methods/Design: We conducted a clinical service evaluation following the introduction of 400µg OTFC lozenges within London's Air Ambulance (LAA) for the provision of pre-hospital analgesia. Our primary objective of the study was to identify potential benefits and limitations for the OTFC lozenge's adoption as a pre-hospital analgesic option in LAA's civilian response to a MCI. We retrospectively analysed all major trauma patients attended to by LAA between 1 st January 2019 and 31 st December 2020 who received a OTFC lozenge. We evaluated the patients' mechanism of injury, initial vital signs and at handover at an Emergency Department (ED) and the need for additional rescue analgesia or sedation. We collected data on any adverse features including nausea, drowsiness or respiratory depression. Results/Conclusions: 190 patients were included in the data set, the majority having suffered penetrating trauma. We identified an increased need for rescue analgesia and sedation in blunt trauma patients requiring prolonged extrication or limb reduction. 1% (n=2) of patients presented with nausea requiring withdrawal of the lozenge. No patients had adverse features following use of the OTFC lozenge. Our findings were comparable to previous literature on the use of OTFC lozenges. We argue that the OTFC lozenge has shown to be a safe and rapid method of delivering pre-hospital analgesia during LAA's routine work. It has the advantage of not requiring intravenous (IV) access and presents a robust option for pre-hospital analgesia during a MCI.